Exergy Analysis of Multistage Axial Flow Compressor - Tolba, Hisham; El-Maksoud, Rafea A.; Emara, Kareem (Eximia, 2022)
The air compressor is one of the most important devices for many processing industries and the power generation sector. Therefore, the present paper aims to study multi-stage axial flow compressors, especially for thermal power stations. Energy and exergy analysis is used to demonstrate different parameters in the compressor performance and its different stages, where 12 stages are considered; as an example. It is paramount to determine the working parameters such as compressor inlet temperature, inlet relative humidity stage pressure ratio, and the stage’s polytopic efficiency at different stages. The results illustrate that the second law efficiency, exergy destruction, and exergy destruction ratio have different behaviors. Whereas, in the last stages compared with the early stages, the exergy destruction ratio is decreased with the increase of stage number, the compressor inlet temperature, the polytropic efficiency, and the stage pressure ratio. This effect is very small; in all compressor stages and could be neglected. Also, the effect of relative humidity changes on air mass flow rate ratio, exergy destruction ratio, and power consumption; throughout each stage, and overall, the compressor; is very small and could be neglected. On the other hand, for each stage and overall compressor, the results indicate that the increase in inlet air temperature leads to decreasing power consumption. In addition, the effect of inlet air temperature changes on exergy destruction ratio may be neglected, as the maximum change of exergy destruction ratio is about 1% when increasing inlet air temperature by about 25oK.